A New Genus and Species of Chiggers (Trombidiformes: Leeuwenhoekiidae) from Peru - Bassini-Silva, Ricardo; Huang-Bastos, Matheus; Oconnor, Barry M; Klimov, Pavel; Welbourn, Cal; Ochoa, Ron; Barros-Battesti, Darci Moraes [UNESP]; De Castro Jacinavicius, Fernando (Oxford University Press (OUP), 2021)
South American chiggers have historically been poorly studied, and this has continued into present times. Of the 33 genera in the family Leeuwenhoekiidae Womersley, only Odontacarus Ewing and Sasacarus Brennan & Jones have been reported in Peru. Here, we describe a new genus, Peruacarus n. gen., and a new species, Peruacarus anthurium n. sp., parasitizing Koford's grass mouse, Akodon kofordi Myers & Patton, in Peru.
Keywords: chigger mite; ectoparasite; Peru; Rodentia; South America